(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: To determine the assigned values and evaluate the Z-score performance of laboratories participating in an external quality assessment pilot study for coagulation testing. Methods: Coagulation external quality assessment samples at 3 concentration levels were produced and distributed to 67 participating laboratories in Ho Chi Minh city, Hue, and the Mekong Delta region. Robust statistical methods, in accordance with ISO 13528:2022, were employed to establish assigned values for PT, APTT, and fibrinogen based on participant data. The study further assessed the percentage of laboratories achieving acceptable Z-score across three major instrument platforms: Sysmex CS series, Stago Compact Max, and ACL TOP series. Results: The assigned values for PT and APTT exhibited variations exceeding 10%, primarily due to methodological discrepancies between different instrumentation platforms. Regarding Z-score performance, 100% of laboratories achieved acceptable scores for fibrinogen, while the success rates for APTT and PT were over 85% and 70%, respectively. Conclusions: This study provides a comprehensive overview of the current status of laboratory performance, serving as a basis for quality monitoring, training, and continuous improvement. The findings establish a significant foundation for the broader implementation of coagulation external quality assessment programs in the near future.